Missense variant in interleukin-6 signal transducer identified as susceptibility locus for rheumatoid arthritis in Chinese patients - Khai Pang Leong; Mei Yun Yong; Liuh Ling Goh; Chia Mun Woo; Chia Wei Lim; Ee Tzun Koh (Archives of Rheumatology, 2021)
Objectives: This study aims to uncover variants of large effect size and allele frequency below 5% by sequencing all extant genes associated with rheumatoid arthritis (RA) in a homogeneous patient cohort. Patients and methods: This retrospective study was conducted between January 2001 and December 2017. We selected Chinese RA patients positive for anti-citrullinated peptide antibody (ACPA). All the 128 known candidate genes identified through genome-wide association studies were sequenced in 48 RA patients (15 males, 33 females; mean age 53.32±8.98 years; range, 32 to 75 years) and 45 controls (11 males, 34 females; mean age 32.18±9.54; range, 21 to 57 years). The exonic regions of these genes were sequenced. The resultant data were analyzed for association using single variant association and pathway-based association enrichment tests. The genetic burden due to low-frequency variants was assessed with the C-alpha test. The candidate variants that showed significant association were validated in a larger cohort of 500 RA cases (71 males, 429 females; mean age 48.6±12.2 years; range, 24 to 92 years) and 500 controls (66 males, 434 females; mean age 32.3±10.1 years; range, 21 to 73 years). Results: Thirty-nine variants in 21 genes were identified using single variant association analysis and C-alpha test, with stepwise filtering. Among these, the missense variant in interleukin-6 signal transducer (IL-6ST) 5:55260065 (p.Cys47Phe) was significantly associated with RA in Chinese patients in Singapore. Conclusion: Our results suggest that a mutation in IL-6ST (5:55260065) confers risk of RA in Chinese patients in Singapore.